Insights into Terminal Sterilization Processes of Nanoparticles for Biomedical Applications - Sergio A. Bernal-Chávez; María Luisa Del Prado-Audelo; Isaac H. Caballero-Florán; David M. Giraldo-Gomez; Gabriela Figueroa-Gonzalez; Octavio D. Reyes-Hernandez; Manuel González-Del Carmen; Maykel González-Torres; Hernán Cortés; Gerardo Leyva-Gómez (Molecules, 2021)
Nanoparticles possess a huge potential to be employed in numerous biomedical purposes; their applications may include drug delivery systems, gene therapy, and tissue engineering. However, the in vivo use in biomedical applications requires that nanoparticles exhibit sterility. Thus, diverse sterilization techniques have been developed to remove or destroy microbial contamination. The main sterilization methods include sterile filtration, autoclaving, ionizing radiation, and nonionizing radiation. Nonetheless, the sterilization processes can alter the stability, zeta potential, average particle size, and polydispersity index of diverse types of nanoparticles, depending on their composition. Thus, these methods may produce unwanted effects on the nanoparticles’ characteristics, affecting their safety and efficacy. Moreover, each sterilization method possesses advantages and drawbacks; thus, the suitable method’s choice depends on diverse factors such as the formulation’s characteristics, batch volume, available methods, and desired application. In this article, we describe the current sterilization methods of nanoparticles. Moreover, we discuss the advantages and drawbacks of these methods, pointing out the changes in nanoparticles’ biological and physicochemical characteristics after sterilization. Our main objective was to offer a comprehensive overview of terminal sterilization processes of nanoparticles for biomedical applications.